The Influence Of ESG (Environmental, Social, Governance) and Company Size On Financial Performance - Yasinta Nurhayati Sonya; Risal Rinofah; Pristin Prima Sari (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study employed a quantitative method with a causal associative approach. The sample was determined through purposive sampling and selected 37 energy sector companies that met the criteria, resulting in 185 observations over the five years of the study. Data analysis was performed using multiple linear regression, preceded by classical assumption tests, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. Based on the analysis, the Environmental variable significantly impacted the financial performance (ROA) of energy sector companies, with a positive regression coefficient of 0.263 and a significance value of 0.037. The Social variable significantly impacted financial performance (ROA), with a regression coefficient of 0.308 and a significance value of 0.032. The governance variable significantly influences financial performance (ROA), with a regression coefficient of 0.0276 and a significance value of 0.028. Firm size has the strongest and most significant influence on financial performance (ROA), with the largest regression coefficient of 0.715 and a significance value of 0.000.